An experiment on supply function competition - Bolle, Friedel; Grimm, Veronika; Ockenfels, Axel; del Pozo, Xavier (European Economic Review, 2013)
We experimentally investigate key predictions of supply function equilibrium. While, overall, equilibrium organizes bidding behavior well, we observe three important deviations. First, bidding is sensitive to theoretically irrelevant changes of the demand distribution. Second, in a market with symmetric firms we observe tacit collusion in that firms provide less than the predicted quantities. Third, in a market with asymmetric capacities, the larger firm bids more competitively than predicted, while the smaller firms still provide less than equilibrium quantities.
Keywords: Supply function competition; Experiment; Demand uncertainty; Asymmetric firms